The Digital Transformation of Healthcare in The Digital Economy: A Systematic Review - Pongsakorn Limna (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
This review article aimed to assess the existing literature regarding the digital transformation of healthcare in the digital economy. The review employed narrative synthesis. Moreover, this systematic review made use of a number of databases, including EBSCO, Google Scholar, Scopus, Web of Science, and ScienceDirect. The documentary method and content analysis were used via systematic review to analyze the data. The review of literature suggested that digital technologies have the potential to improve healthcare delivery, enhance patient outcomes, and increase access to healthcare services. The studies reviewed in this article demonstrate that digital transformation in healthcare can lead to improved efficiency, reduced costs, increased patient satisfaction, and better patient outcomes. The use of digital technologies such as telemedicine, electronic health records, wearables, and mobile health applications has already started to revolutionize healthcare delivery. However, the adoption of these technologies is not without its challenges, including privacy and security concerns, regulatory barriers, and resistance from healthcare providers. It is therefore important for healthcare organizations and policymakers to address these challenges and implement strategies to ensure the effective integration of digital technologies into the healthcare system. Overall, the findings suggest that the digital transformation of healthcare is a critical area of research that has the potential to significantly transform the healthcare industry and improve health outcomes for individuals and communities.